ROLE OF ENVIRONMENTAL FACTORS ON THE BACTERIAL BLIGHT (BLB) DISEASE OF COTTON CAUSED BY XANTHOMONAS CAMPESTRIS PV. MALVACEARUM UNDER SOUTH GUJARAT CONDITION - PRASHANT; B. SANDIPAN; H. R. DESAI; B. G. SOLANKI (The Bioscan, 2015)
Bacterial blight disease was recorded with its first appearance and subsequently at weekly interval till it prevailed on G. Cot. Hy. 12 variety. Result shows that disease was first appeared in 36 th Met. week (First week of September) with 1.37 % intensity and prevailed up to 48 th Met. Weeki.e.last week of November (1.75 %) with its peak during 42 nd week i.e. 2 nd week of October (24.50 %) for the year 2012-13. And for 2013-14, indicates that the disease was first appeared in 32 nd standard week (First week of August) with 2.66% intensity and prevailed up to 47 th Met. Week i.e third week of November (1.37%) with its peak during 38 th week i.e.September 3rd week (24.75 %) and then it gradually decreased. Bacterial leaf blight has positive correlation with the environmental factors